Saint Vicent of Paul and Prayer (Teología, 2015)
St Vincent de Paul appears not only as the saint who protects the poor, but as a prayer teacher. This article refers to this aspect in particular. It intents to show how St Vincent takes into account prayer and devotion. St Vincent belongs to the XVIIth century, so he is distinguished by thoroughness and he will let us know, in detail, how prayer can be carried on. In his opinion prayer opens the individual’s heart to brotherly charity and to the service of suffering people. Thus, prayer allows us to completely fulfil GOD’s WILL. Summing up in his own words we can say: “Give me a human being embracing prayer, and he will be capable
Keywords: Prayer; Devotion; Charity; Service of the Poor